Safety or Style? An Examination of the Role of Football Equipment Personnel - Brent D. Oja; Jordan R. Bass (Journal of Applied Sports Management, 2016)
The national recognition of concussions has increased greatly over the past de-cade. While concussions have moved to the spotlight, institutional policies and procedures are just beginning their climb into the public eye. This research delves into a sphere of sport that has to date been largely ignored, the role of equip-ment personnel. Equipment personnel were chosen due to their connection to concussions and organizational power. Organizational power has traditionally rested with those who acquire the most resources. Coaches usually represent such power. However, power can also be derived from maintaining resources. Quali-tative methodology was utilized to gauge the perceptions of equipment person-nel on a variety of topics related to organizational power and concussions. The results revealed that equipment personnel have little overall professional power. Although a majority of participants reported that they believed they retained the power to choose protective equipment for student-athletes, this autonomy was neither consistent nor sovereign. Informal power structures were discovered in which coaches were thought to have more power than their formal supervisors. Administrators should consider implementing policies that grant greater autono-my to equipment personnel in order to better protect student-athletes.
Keywords: Concussions; Power; Hierarchy; Structure